Hungary in journalism of Roman Dmowski (based on „Polish Politics and the Rebuilding of the State”) - Kowalczyk, Michał (Saeculum Christianum. Pismo Historyczne, 2021)
Roman Dmowski was a Polish politician and an ideological father of National Democracy. He was a very important figure for the restoration of Poland’s independence after the First World War. In 1925 he published his famous book entitled “Polish Politics and the Rebuilding of the State”. He explained his motives for an anti-German policy before and during the First World War. This article is focused on his relations with Hungary. Despite the tradition of Polish-Hungarian friendship, Roman Dmowski represented a rather unfriendly position towards Hungary considering policy of Budapest as favorable to Germany. Therefore, Roman Dmowski was a follower of an alliance with Prague and Bucharest instead